The dynamism of communication technology adoption, market information and welfare: evidence from Nile perch (Lates niloticus) fish market, Mwanza, Tanzania - Kitole, Felician; Lihawa, Robert; Sesabo, Jennifer; Shitima, Christina (Likes & Reservoirs : science, policy and management for suistanable use, 2024)
A research paper submitted to the Likes & Reservoirs :science, Policy and Management for sustainable use,Vol.28 of 2023.